NAD- and NADP-dependent 11 beta-hydroxysteroid dehydrogenase isoforms in guinea pig kidney with gossypol inhibition - Wang Mao-Shan; Lorenzo Beverly J; Reidenberg Marcus M (Acta Pharmacologica Sinica, 2016)
AIM: To study the mechanism of gossypol-induced hypokalemia. METHODS: The 11 beta-hydroxysteroid dehydrogenase (11 beta-OHSD) protein was prepared from guinea pig kidney. The activity of 11 beta-OHSD with NAD or NADP as the coenzyme was measured by HPLC in both control and gossypol treatment. RESULTS: The Vmax and K(m) were 0.64 mmol.h-1/g protein and 0.07 mumol (cortisol) for NAD-dependent 11 beta-OHSD, 1.75 mmol.h-1/g protein and 0.21 mumol (cortisol) for NADP-dependent 11 beta-OHSD, respectively when 80 micrograms of enzyme protein was used. The inhibitory effects of gossypol on these two 11 beta-OHSD isoforms were different. The IC50 (95% confidence limits) were 50.2 (48.3-52.0) mumol of gossypol for NAD-dependent 11 beta-OHSD and 1143 (1098-1188) mumol of gossypol for NADP-dependent 11 beta-OHSD. The Ki was gossypol 96 mmol.L-1 for the former and 340 mmol.L-1 for the latter. CONCLUSION: The NAD-dependent 11 beta-OHSD is a more critical physiologic mechanism than NADP-dependent 11 beta-OHSD for hypokalemia caused by gossypol.